Development of high-sensitive ELISA method for detection of adipophilin levels in human colostrum and breast milk - Mitrova, Katarina; Karpisek, Michal; Durilova, Marianna; Dragusin, Lavinia Gabriela; Nevoral, Jiri; Bronsky, Jiri (Journal of clinical laboratory analysis, 2014)
AIM: To develop and validate high-sensitive (hs) ELISA method for detection of adipophilin (adipose differentiation-related protein, ADRP) in human breast milk (BM) and to analyze adipophilin levels in BM during 12 months of lactation. METHODS: ADRP levels were determined using hsELISA method (Biovendor-Laboratory Medicine, Inc.) in colostrum (D0) and BM of 72 mothers was collected 1, 3, 6, and 12 months following delivery (M1, 3, 6, 12). RESULTS: ADRP was detectable in BM up to 12 months of lactation. Mean levels at D0 were 1.98 ± 0.12; M1, 2.83 ± 0.21; M3, 2.39 ± 0.17; M6, 2.57 ± 0.16; and at M12 3.25 ± 0.21 μg/ml. Significantly higher levels of ADRP were found in M1 and M12 when compared to D0 and in M12 when compared to M3 (overall P = 0.0001). No significant correlation was seen between ADRP levels in BM and adiponectin, body weight of infants, their birth length, body weight gain during the first year of life, or BMI of mothers before pregnancy. CONCLUSIONS: We developed and validated hsELISA for detection of ADRP in human BM. ADRP was detectable in human BM during the whole 12 months of lactation period and its levels were intraindividually well-conserved.
Keywords: Membrane Proteins; Pregnancy; Humans; Perilipin-2; mateřské mléko; Female; Colostrum; nutritional programming; ELISA; lidé; Enzyme-Linked Immunosorbent Assay; časové faktory; kolostrum; ženské pohlaví; Milk, Human; laktace; human breast milk; adipophilin; perilipin 2; těhotenství; ADRP; membránové proteiny; Lactation; Time Factors